Semi-occluded vocal tract exercises in the rehabilitation of recurrent paralysis: A case study. - Jara Cabrera, Gerson; Alarcón Vega, Raúl; Medina Valdebenito, Damián (Revista de Investigación en Logopedia, 2021)
The object of the present work is to show the effectiveness of a sequence of exercises for the semi-occluded vocal tract in the rehabilitation of a vocal clinical case diagnosed with unilateral recurrent paralysis. The exercises for the semi-occluded vocal tract are a series of postures which involve artificial enlargement or narrowing of the vocal tract in order to increase impedance and generate improvements in the vibration of the vocal cords. These exercises fit into the tendency towards physiological rehabilitation, which seeks to re-establish a balance between the three sub-systems involved in voice production (respiration-phonation-resonance) simultaneously, in contrast to the traditional tendency towards a symptomatological approach. The physiological tendency is based on the principles of sensorimotor learning, which pursues real changes in the pattern of voice production that will be maintained over time.Fifteen sessions of vocal therapy were carried out with exercises of the semi-occluded vocal tract. To assess the changes in the voice, initial and final evaluations were carried out with fiberoptic nasolaryngoscopy, acoustic analysis by measurement of disturbance and spectral analysis, perceptual study using the GRBASI scale evaluated by a committee of external judges, maximum phonation time and the patient's own evaluation. After treatment, improvements were recorded in the voice and it is concluded that exercises of the semi-occluded vocal tract can be an effective tool for treating pathologies of this type.
Keywords: semi-occluded vocal tract; unilateral recurrent paralysis; physiological rehabilitation